Prevalence of Bancroftian Filariasis among Edim Otop sub-urban dwellers in Calabar Municipality of cross river state, Nigeria - Ekanem I. A., Alaribe A .A .A, Ekanem A.P. (Journal of Applied Pharmaceutical Science)
Study on the prevalence of brancroftian filariasis among sub-urban dwellers of Edim Otop Community in Calabar, Nigeria was carried out between April and November, 2009. Two hundred and twenty two willing participants within the age range of 15-55 years, from 5 designated zones were randomly selected for the collection of day and night blood samples for screening by ICT card test and Knott’s concentration methods respectively for Wuchereria bancroftian antigen and microfilaria. The participants were made up of 129 males (56.31%) and 92 females (43.69%). The numbers of positive cases obtained by the highly sensitive ICT card test were 38 (17.20%). There was no positive case by the conventional Knott’s concentration method. The highest number of positive cases (4.5%) was obtained from Edim Otop Close and Bassey Oqua zones with 40 and 38 participants, while the least number of positive cases (2.2%) were obtained from Edim Otop Crescent and University of Calabar Satellite town as compared to other zones of the study. . The highest (15.85%) antigenaemia were observed within the ages of 37-47 and the least (0.9%) within 15-25 years old participants. A higher percentage of positive cases were recorded among male participants (57.89%) than females (42.11%). There was no significant difference (P>0.05) in the distribution of parasites according to age and gender in the study area using Chi square methods. Edim Otop Community in Calabar, Cross River State is presented in this study as having shown positive cases of antigenaemia due to Wuchereria bancrofti.
Keywords: Bancroftian Filariasis, Edim Otop Sub-Urban dwellers, Nigeria.